2023
DOI: 10.7554/elife.82705
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative exhausted CD8+ T cells exacerbate long-lasting anti-tumor effects in human papillomavirus-positive head and neck squamous cell carcinoma

Abstract: The survival prognosis of human papillomavirus (HPV)-positive and HPV-negative head and neck squamous cell carcinoma (HNSCC) is largely different, and little is known about the anti-tumor mechanism of tumor-infiltrated exhausted CD8+ T cells (Tex) in HNSCC. We performed cell-level multi-omics sequencing on human HNSCC samples to decipher the multi-dimensional characteristics of Tex cells. A proliferative exhausted CD8+ T cell cluster (P-Tex) which was beneficial to survival outcomes of patients with HPV-positi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 52 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…Previous studies have shown that CDK1 and CDK inhibitors could regulate the IFN pathway ( 46 , 47 ). Emerging evidence also suggests that CDK4 , another member of the CDK family may affect T-cell survival ( 48 ). In this study, we have identified relevant targets of CDK1 , such as GALNT2 and VCAM1 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that CDK1 and CDK inhibitors could regulate the IFN pathway ( 46 , 47 ). Emerging evidence also suggests that CDK4 , another member of the CDK family may affect T-cell survival ( 48 ). In this study, we have identified relevant targets of CDK1 , such as GALNT2 and VCAM1 .…”
Section: Discussionmentioning
confidence: 99%
“… 25 In female mice, intravaginal immunization with HPV followed by boosting with different HPV serotypes resulted in a 10-fold increase in cervicovaginal antigen-specific CD8+ T cells compared to priming alone. 12 While “exhausted” CD1+ HPV-specific CD8+ T cell clusters have been observed in the context of HPV-positive head and neck squamous cell carcinoma (HNSCC), 26 , 27 this cluster contributes to persistent anti-tumor immunity due to their extended cell survival and specialized cytotoxic capacity. 26 Moreover, it has been associated with longer survival in HPV-positive HNSCC.…”
Section: The Immune Reaction To Carcinogenic Virusesmentioning
confidence: 99%
“… 12 While “exhausted” CD1+ HPV-specific CD8+ T cell clusters have been observed in the context of HPV-positive head and neck squamous cell carcinoma (HNSCC), 26 , 27 this cluster contributes to persistent anti-tumor immunity due to their extended cell survival and specialized cytotoxic capacity. 26 Moreover, it has been associated with longer survival in HPV-positive HNSCC. 26 Notably, no reports exist of exhausted anti-HPV CD8+ T cells in the context of HPV infection in non-cancerous tissue.…”
Section: The Immune Reaction To Carcinogenic Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers consider IR co-expression as an indication of T cell exhaustion, whereas others claim it defines a subset of activated and functional effector cells. 12 , 13 , 14 For example, early exhausted PD-1 + T cells (Tex) cells can be reinvigorated by anti-programmed cell death-ligand 1 (PD-L1) treatment, whereas terminally exhausted Tex cells expressing PD-1, LAG3, or TIM3 are unresponsive to anti-PD-1 or PD-L1 treatment. 15 The impact on anti-tumor response and potential change of co-expression pattern of IRs after immune checkpoint inhibitor (ICI) treatment remains unclear.…”
Section: Introductionmentioning
confidence: 99%